Effects of Home Education Guidance Services and Improvement Measures: An Analysis Based on Survey Data of 1,850 Families in Hubei Province - Lei, Wanpeng (Best Evidence in Chinese Education, 2024)
Home education guidance services play an important role in enhancing the quality of home education and supporting child healthy and holistic development. Based on survey data of 1,850 families from eight cities and 18 counties in Hubei Province, this study examined the effects of home education guidance services on parental education literacy, parental education involvement, and child development. Ordinary least squares regression (OLS) and propensity score matching (PSM) were used in the analysis. The purpose of this article was to provide implications for improving the effectiveness of home education guidance.